Seminars and interactive lectures as a community of knowledge co-construction: The use of modifiers. (April 2015) - Lin, Chia-Yen
Abstract: The present study extends previous research by comparing the use of modifiers in seminars and interactive lectures in BASE and MICASE with a twofold purpose: firstly, to reveal how they constitute essential discourse properties, shedding new light on generic similarities and differences between the two modes of instruction; and secondly, to determine further whether the employment of these linguistic devices is more sensitive to generic norms or to British/North American academic cultures. The results of the study show that the interplay of diverse modifiers in various participatory mechanisms tends to highlight individual contributions with emphatic elements for a stance-securing effect, while at the same time softening contributions to enact a humble knower persona and signal a need for open discussion. The functional homogeneity of modifiers implies that seminars and interactive lectures are exemplars of a genre of knowledge co-construction on the one hand, and on the other, it confirms that the influence of generic norms outweighs that of British/North American academic cultures regarding the functions of these linguistic devices. However, possible generic variation between the exemplars as well as academic cultures contribute to significant statistical discrepancies in particular modifiers between the corpora. Highlights: The study compares modifiers in seminars and interactive lectures in BASE and MICASE. Generic norms and academic cultures are considered. Functions of modifiers depend on generic norms. Seminars and interactive lectures are exemplars of a knowledge co-construction genre. Variations between the exemplars and academic cultures inform distribution patterns.